Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3109/09687688.2010.525756
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin regulates SNARE protein expression and phagocytosis in dendritic cells

Abstract: Since being introduced globally as Aspirin in 1899, acetylsalicylic acid (ASA) has been widely used as an analgesic, immune-regulatory, anti-pyretic and anti-thrombotic drug. ASA and its metabolite, salicylate, were also reported to be able to modulate antigen presenting functions of dendritic cells (DC). However, the intracellular targets of ASA in DC are still poorly understood. Since phagocytosis is the initial step taken by antigen-presenting cells in the uptake of antigens for processing and presentation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…However, Stx11 −/− BMDCs appeared not impaired in any of the activities investigated. Our results partially mirror previous findings that report that the ability of VTI1B-and VAMP8-deficient DCs to process antigen and stimulate the proliferation of CTLs was not reduced [18], although an inhibitory role for VAMP8, VTI1A and VTI1B was found in murine immature DC phagocytosis [24,25].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, Stx11 −/− BMDCs appeared not impaired in any of the activities investigated. Our results partially mirror previous findings that report that the ability of VTI1B-and VAMP8-deficient DCs to process antigen and stimulate the proliferation of CTLs was not reduced [18], although an inhibitory role for VAMP8, VTI1A and VTI1B was found in murine immature DC phagocytosis [24,25].…”
Section: Discussionsupporting
confidence: 91%
“…However, Stx11 −/− BMDCs appeared not impaired in any of the activities investigated. Our results partially mirror previous findings that report that the ability of VTI1B-and VAMP8-deficient DCs to process antigen and stimulate the proliferation of CTLs was not reduced [18], although an inhibitory role for VAMP8, VTI1A and VTI1B was found in murine immature DC phagocytosis [24,25].Next, we have reported that STX11 is constitutively expressed in BMMCs at the mRNA level and regulated upon LPS or IgE/Ag treatment. Again despite upregulation, STX11 deficiency does not affect BMMC degranulation activity based on LAMP-1/ CD107a and β-hexosaminidase measurements.…”
supporting
confidence: 91%
“…the cell type studied here) identified the Q-SNAREs stx7, stx8 and stx12 on phagosomes (Buschow et al, 2012). The presence of SNAP23, stx7, stx12 and Vti1b on phagosomes has been confirmed by immunofluorescence, cellular fractionation and overexpression of tagged fusion proteins (Cai et al, 2011; Cebrian et al, 2011; Collins et al, 2002; Fratti et al, 2003; Nair-Gupta et al, 2014; Sakurai et al, 2012). Third, levels of cytochrome b 558 on phagosomes correlate with phagosomal SNAP23 in a macrophage cell line (Sakurai et al, 2012), and gp91 phox trafficking and ROS production could be inhibited by targeting SNAP23 in primary human neutrophils (Uriarte et al, 2011), suggesting a role for this SNARE in the phagosomal recruitment of NOX2 in dendritic cells.…”
Section: Resultsmentioning
confidence: 79%
“…The Qb-SNARE Vti1a, which is weakly homologous to Vti1b (28% sequence identity), locates at the Golgi network (172,335) and endosomes (39). Vti1a also locates at phagosomes (38,44,286), with quantitative proteomics showing a decreased phagosomal presence over time of uptake (FIGURE 5). Although Vti1a knockout mice are viable (177), they show behavioral, metabolic, and growth defects (170).…”
Section: B Vti1amentioning
confidence: 99%
“…Although Vti1a knockout mice are viable (177), they show behavioral, metabolic, and growth defects (170). Vti1a not only plays a role in Golgi trafficking, with depletion of Vti1a resulting in a disruption of the ribbon structure of the Golgi apparatus (285), but can also act as a negative regulator of phagocytosis (44). Vti1a mediates retrograde trafficking from late endosomes to the trans-Golgi network by complexing with Stx16 (Qa), Stx10 (Qc), and VAMP3 (R) and trafficking from early/recycling endosomes with Stx16, Stx6 (Qc), and VAMP4 (R) (105,172,193,305).…”
Section: B Vti1amentioning
confidence: 99%